Digital Economy, Startups and Innovation By 2047 - Ashwini Patil, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
The journey towards 2047 marking centenary of India’s Independence will be strongly shaped by the risk of the digital economy, startup and innovations.The digital economy is expected to become backbone of National growth contributing a significant share to GDP through E-Commerce, AI, Green Hydrogen and digital governance. As the nation aspire to become a developed country by 2047 the digital economy supported by innovative startup and Breakthrough technologies will serve as simultaneously, startup will fuel employment, inclusive growth and global competitiveness by solving pressing challenges in sectors like healthcare,Agriculture, Education and energy more ever continuous innovation in areas in such as robotics, biotechnology, space technology and green energy will ensure sustainable development.
Keywords: Viksit Bharat; digital economy; innovation; startups; Artificial intelligence